ANSYS Modelling and Vibration Stability Analysis of Pipelines Conveying Fluid - GABAN, IVAN (IRC, 2017)
Material engineering has develop considerably over the year to the extent it has allow cost reduction in testing, therefore making studies relevant to the vibrational stability of pipelines conveying fluid to become more important than ever. The research for this field has grown considerably over the year, but there are still some gaps which have yet to be covered. One of said gap is the hypothesis that a natural frequency of pipeline is subjected to the presence and absence of fluid flow within it. Thus, to prove the hypothesis and expand the understanding of fluid-structure interaction uncertainty, this project aims to present the ANSYS model of pipelines conveying fluid where the presence and absence of fluid flow are varied. The proposed model geometry will be a straight, tight and horizontal pipe with fluid passing through it. The model will then be simulated using the ANSYS CFX Solver and the resultant data tabulated and analysed. Additionally, comparisons were also made with previous research paper as to verify the results. In the end, the results show that fluid flow within the pipeline has little to no effect on its natural frequency.